2020
DOI: 10.1038/s41467-019-13926-4
|View full text |Cite
|
Sign up to set email alerts
|

Mikania micrantha genome provides insights into the molecular mechanism of rapid growth

Abstract: Mikania micrantha is one of the top 100 worst invasive species that can cause serious damage to natural ecosystems and substantial economic losses. Here, we present its 1.79 Gb chromosome-scale reference genome. Half of the genome is composed of long terminal repeat retrotransposons, 80% of which have been derived from a significant expansion in the past one million years. We identify a whole genome duplication event and recent segmental duplications, which may be responsible for its rapid environmental adapta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
75
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 92 publications
(91 citation statements)
references
References 66 publications
3
75
0
1
Order By: Relevance
“…By surveying in vitro plantlets, the genomic characteristics may be assessed more accurately. The genome size of M. cordata was estimated at 1.80 Gb, which is typical in Asteraceae [50] and comparable with its congeneric M. micrantha of 1.86 Gb [13]. However, this size is much smaller than that of Helianthus annuus (3.6 Gb) [51].…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…By surveying in vitro plantlets, the genomic characteristics may be assessed more accurately. The genome size of M. cordata was estimated at 1.80 Gb, which is typical in Asteraceae [50] and comparable with its congeneric M. micrantha of 1.86 Gb [13]. However, this size is much smaller than that of Helianthus annuus (3.6 Gb) [51].…”
Section: Discussionmentioning
confidence: 89%
“…Nevertheless, our results highlight that the genome size of invasive species can be larger than that of the native species. We speculate that the large genome of M. micrantha may be associated with its CAM photosynthetic characteristics [13], since CAM plant tends to have low stomatal density [54], which is further negatively correlated with genome size [55]. Moreover, the estimated repetitive rate of M. cordata (78.35%) is found higher than that of most published genomes of Asteraceae plants, such as M. micrantha (73.12%) [13], Erigeron breviscapus (54.58%) [56], and Taraxacum kok-saghyz (68.56%) [57].…”
Section: Discussionmentioning
confidence: 93%
“…Microorganisms are major members of the soil P cycle, improving available P to plants (Khan et al, 2009). We have previously reported that the available P content in M. micrantha rhizosphere was significantly higher than that in the rhizosphere of two native plants (Liu et al, 2020).…”
Section: Enrichment Of Pseudomonas and Enterobacter To Enhanced Phospmentioning
confidence: 80%
“…Mikania micrantha (Asteraceae family), an extremely fast-growing vine, is one of the top 100 worst IAS in the world ( Lowe et al, 2000 ), causing severe substantial damages to natural ecosystems ( Day et al, 2016 ) and economic losses ( Macanawai et al, 2012 ). Several mechanisms have been proposed to explain the success of M. micrantha invasion, such as rapid growth caused by high regeneration capacity of each vine node ( Li X. et al, 2013 ) and extraordinary biological characteristics including high seed production and germination ( Hu and But, 1994 ), the strong allelopathic effects on other native plant and soil microbes ( Chen et al, 2009 ), and high nutrient (NPK) turnover rates in soil ( Sun et al, 2019 ; Liu et al, 2020 ). Recently, we have published the genome of M. micrantha , as well as its rhizosphere metagenome, and also found out that the rhizosphere microbes of M. micrantha could increase the bioavailable nitrogen content to speed up the nitrogen cycle ( Liu et al, 2020 ), which might contribute to its rapid growth as well as invasion.…”
Section: Introductionmentioning
confidence: 99%
“…What's more, the world expansion capability of Cydia pomonella has been informed according to its genome information [19]. Molecular mechanism of rapid growth and invasive adaptation of an invasive species Mikania micrantha has also been investigated according to its reference genome [20]. Therefore, the full-length transcriptome data of P.americana and P.icosandra will contribute to the genomic research and provide insights into invasive mechanism of P.americana through comparative genomics study in Phytolaccaceae species.…”
Section: Discussionmentioning
confidence: 99%